Decreased mortality in traumatic brain injury following regionalization across hospital systems. Issue 4 (April 2015) - Kelly, Michael L.; Banerjee, Aman; Nowak, Michael; Steinmetz, Michael; Claridge, Jeffrey A.
Abstract : BACKGROUND: The Northern Ohio Trauma System (NOTS) was established to improve outcomes of trauma patients across the region. We hypothesized that mortality in patients with traumatic brain injury (TBI) would improve after regionalization. METHODS: All patients older than 14 years with a TBI were identified from NOTS, a regional trauma system consisting of two large health care systems and regional emergency medical services providers. Data from 2008 through 2012 were analyzed before and after NOTS formation in 2010. Multivariate logistic regression analysis was performed to evaluate independent predictors of survival. RESULTS: A total of 11, 220 patients were identified with TBI in the NOTS database, 4, 507 (40%) before NOTS and 6, 713 (60%) after NOTS formation. Admissions to the regional Level 1 center post-NOTS formation increased from 36% to 46% ( p < 0.0001). Injury Severity Scores (ISSs) and Abbreviated Injury Scale (AIS) scores were similar between periods. The mortality rate decreased from 6.2% to 4.9% ( p = 0.005) among all TBIs and from 19% to 14% ( p < 0.0001) in TBIs with a head AIS score of 3 or greater (n = 3, 538). Craniotomy procedures increased from 1.8% to 2.7% ( p = 0.003) overall and from 5.9% to 8.1% ( p = 0.02) in TBIs with head AIS score of 3 or greater. Logistic regression analysis demonstrated an independent effect on survival for post-NOTS period in all patients (odds ratio, 0.76; 95% confidence interval, 0.62–0.94; C statistic = 0.96) and in TBIs with head AIS score of 3 or greater (odds ratio, 0.72; 95% confidence interval, 0.58–0.89; C statistic = 0.86). CONCLUSION: Regionalization of trauma care across hospital systems is associated with a reduced mortality rate for patients with TBI, particularly for patients with a head AIS score of 3 or greater. Mortality decreased by 24% for all TBIs and by 28% for severe TBIs. These findings support regionalization of trauma care with collaboration and consolidation of care across health care systems. LEVEL OF EVIDENCE: Therapeutic/care management, level IV; epidemiologic study, level III.